A high-bonding meta-aramid filament and its preparation method and application
By physically and chemically modifying the surface of the meta-aramid filament, forming a network-like surface structure and introducing active groups, the problem of insufficient binding force between fiber and functional materials is solved, and higher mechanical properties and stability are achieved, and it is suitable for the application of self-lubricating materials.
Patent Information
- Application Number
- CN202411907628.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The surface activation performance of existing meta-aramid filaments is insufficient, resulting in weak interface bonding between fibers and functional materials, limiting their application in the field of self-lubricating.
Using surface functionalization technology combining physical modification and chemical modification, a network-like surface structure is prepared through high-pressure airflow construction technology to increase the roughness of the fiber surface and introduce active groups on the fiber surface to enhance the binding force between the fiber and the resin matrix.
It improves the bonding strength between the fiber surface modifier and the fiber, improves the index stability of the fiber, improves the mechanical properties and whiteness of the meta-aramid network wire, and is suitable for the field of self-lubricating materials.
Smart Images

Figure CN119332511B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-bonding meta-aramid filament and a preparation method and application thereof, belonging to the technical field of meta-aramid spinning. Background Art
[0002] Meta-aramid filament is one of the meta-aramid product series. It not only has the excellent flame retardancy (limiting oxygen index > 29%), thermal stability, chemical stability, radiation resistance, and wear resistance of meta-aramid, but also has superior mechanical properties and good weavability. It is widely used in protective clothing processing, rubber reinforcement, optical cable sheathing, electrical insulation and other fields.
[0003] In recent years, meta-aramid filaments have extremely high hardness and wear resistance, can withstand heavy loads and high-speed movement, and can be composited with functional materials to form self-lubricating fiber fabric lining materials, which are used as key basic raw materials for aviation self-lubricating spherical bearings. This basic raw material plays a vital role in lubrication, isolation, and friction reduction in bearings. It also has functions such as reducing mechanical power consumption, impact resistance, vibration reduction, and noise reduction. Its comprehensive performance directly determines the performance and reliability of self-lubricating spherical bearings. The basic raw material of self-lubricating fabrics is a two-dimensional composite material prepared by a specific process with high-performance filament fiber fabric as the main body and resin as the reinforcing phase, such as the technical solutions disclosed in Chinese patent applications CN113089327A and CN118390292A. However, due to the insufficient activation performance of the aramid fiber surface, the interface bonding force between the fiber and the functional material is weak, and it is subject to many restrictions in the application process in the field of self-lubricating. Therefore, it is of great value to develop a highly laminated meta-aramid filament and its preparation method. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a highly laminated meta-aramid filament and a preparation method and application thereof. The meta-aramid filament has a high degree of roughness, which provides abundant active sites for active groups grafted by the back-end chemical modification technology, and effectively improves the bonding strength between the surface modifier and the fiber surface; the uniform network degree on the surface of the meta-aramid filament effectively improves the fiber fuzziness and improves the stability of fiber indicators (cv value); the mechanical properties of the produced meta-aramid network yarn are improved compared with conventional products, and the whiteness and color are better.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing high-bonding meta-aramid filaments, the preparation method comprising:
[0006] S1. Preparation of dried silk:
[0007] The meta-aramid polymer solution is subjected to dry-jet wet spinning, coagulation forming, stretching, water washing and drying operations to obtain dried yarn;
[0008] S2. Surface structure modification:
[0009] The dried filament bundle enters a filament bundling device, and the surface of the fibers in the filament bundle is structurally modified by a high-pressure airflow to obtain a network-like fiber, which is then rolled up and doffed by a winding machine;
[0010] The filament bundling device comprises a filament path and an air flow channel, wherein the air flow channel is communicated with the side of the filament path, the filament bundle to be surface structure treated passes through the filament path, and high-pressure gas is passed through the air flow channel;
[0011] S3. Heat treatment:
[0012] After the network-like fibers are unwound, they are subjected to heat setting treatment;
[0013] S4, interface enhancement modification:
[0014] The heat-treated fibers are sizing treated, and finally wound and doffed to obtain the highly laminating meta-aramid filament product;
[0015] The sizing emulsion used in the sizing treatment comprises: a self-emulsifying cationic water-based sizing agent, a softener, an antistatic agent and water.
[0016] Furthermore, the silk path is arranged horizontally, the air flow channel is vertically connected to the side of the silk path, and the air pressure in the air flow channel is 2-5 kg / cm 2 of high pressure gas.
[0017] Further, when the fineness of the filament bundle entering the filament bundling device is 50-266D, the diameter of the filament path is 1.8-3.0 mm, the diameter of the airflow channel is 0.7-0.9 mm, and the relationship between the airflow Q in the airflow channel and the high-pressure gas pressure P in the airflow channel is Q=1.043*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle passing through the wire path is 10-20m / min.
[0018] Further, when the fineness of the filament bundle entering the filament bundling device is 300-600D, the diameter of the filament path is 2.0-5.0 mm, the diameter of the airflow channel is 0.9-1.1 mm, and the relationship between the airflow Q in the airflow channel and the high-pressure gas pressure P in the airflow channel is Q=1.353*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle passing through the wire path is 20-40m / min.
[0019] Furthermore, the self-emulsifying cationic water-based sizing agent is an unsaturated polyester sizing agent or a cationic water-based polyurethane sizing agent;
[0020] The unsaturated polyester type sizing agent is prepared by reacting an amino modified resin with isophorone diisocyanate (IPDI); the cationic waterborne polyurethane type sizing agent is prepared by reacting isophorone diisocyanate, 2,2-dimethylol propionic acid and triethylamine;
[0021] In the sizing emulsion, the mass ratio of the self-emulsifying cationic aqueous sizing agent, the softener and the anti-static agent is (18-25): (8-10): (10-12);
[0022] The mass concentration of the sizing emulsion is 5.5-7%.
[0023] Furthermore, in step S4, the sizing rate of the sizing treatment is 0.5-2.0%.
[0024] Furthermore, in step S3, the temperature of the heat setting treatment is 300-450° C., and the spinning speed is 30-50 m / min.
[0025] Furthermore, the specific process in step S1 is:
[0026] S1-1, Spinning: The meta-aramid polymer stock solution passes through a metering pump with a spinning speed of 3-10 m / min, and is accurately metered and squeezed into the spinneret assembly, and the filament bundle is ejected from the spinneret plate into the coagulation bath;
[0027] S1-2, coagulation molding: the filaments ejected from the spinneret are double diffused in a 50-70% mass concentration DMAC aqueous solution, DMSO aqueous solution or NMP aqueous solution to form primary fibers;
[0028] S1-3, stretching: the spun fiber is connected to the spinning disk through a guide wheel, and a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 40-60% is provided in the spinning disk as a secondary coagulation bath. The spun fiber is connected to a washing roller after passing through the spinning disk, and the fiber is stretched 2-5 times by adjusting the speed ratio between the spinning disk and the washing roller. During the stretching process, a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 30-50% is provided;
[0029] S1-4, washing: using immersion washing method, the fiber is washed in two steps: cold and hot water;
[0030] S1-5, drying: the washed fibers are dried at 90-150°C to obtain dried fibers.
[0031] The invention also discloses a high-bonding meta-aramid filament, which is prepared according to the preparation method of the invention.
[0032] The invention also discloses an application of high-laminate meta-aramid filaments, and the meta-aramid filaments are applied in the field of self-lubricating materials.
[0033] The beneficial effects of the present invention are:
[0034] The present invention adopts a surface functionalization technology that combines physical modification (surface structure modification) with chemical modification (interface enhancement modification). The fiber surface is first physically modified, and a network surface structure is prepared using a high-pressure airflow construction technology to obtain a surface roughness with high wettability. The surface is then functionalized and an active group is introduced. The active group serves as a "bridge" group, with one end connected to a high wettability surface and the other end connected to a downstream resin matrix, thereby effectively increasing the bonding force between the fiber surface and the resin matrix and realizing the functionalization of the fiber in the field of self-lubrication.
[0035] In the preparation method of high-bonding meta-aramid filaments of the present invention, the surface structure of the meta-aramid filament bundle is modified, and a filament bundling device is provided in the spinning process. A high-pressure airflow is provided in the bundling device. When the filament bundle passes through the wire path of the bundling device, it is impacted by a jet airflow perpendicular to the wire strips, generating vortices parallel to the wire strips, causing the monofilaments to produce two saddle-shaped movements and high-frequency vibrations in a wave-like reciprocating manner; the filament bundle is first loosened, and then the entire filament bundle passes through the wire path of the bundling device, and the deflected airflow causes each monofilament to be bundled and accelerated to varying degrees; the monofilaments in the middle of the wire path receive the maximum acceleration given by the airflow, while the monofilaments located on the side walls of the wire path flow back, and when When the single filaments carried by the two airflows converge in the fiber path, they become intertwined and entangled, producing entanglement points along the axis of the fiber, namely network nodes, so that the fiber forms a network surface structure. This network surface structure has the following advantages: (1) Its rich surface roughness provides abundant active sites for the active groups grafted by the back-end chemical modification technology, effectively improving the bonding strength between the surface modifier and the fiber surface; (2) The uniform network degree on the fiber surface effectively improves the fiber fuzziness and enhances the stability of fiber indicators (cv value); (3) The produced meta-aramid network yarn has improved mechanical properties compared with conventional products, and has better whiteness and color.
[0036] In the preparation method of the highly laminated meta-aramid filament of the present invention, an interface enhancement modification technology is added at the rear end of the fiber heat treatment, and the modifier adopts a self-emulsifying cationic water-based sizing agent. After the fiber is sizing treated with the modifier, an active group is grafted on the surface structure modification basis, and while retaining the fiber bundling, antistatic and flexibility, the introduced active group acts as a "bridge" group to covalently link with the fiber network surface to form a new grafting layer, and the covalent bond strengthens the bonding force between the fiber interface and the sizing agent to form a stable and strong organic interface layer, so that the fiber surface has new characteristics, and the modified meta-aramid network silk product maintains the original excellent physical indicators of the fiber. When the fiber fabric is laminated with the resin matrix, the group grafted on the fiber surface can improve the mechanical anchoring between the fabric and the resin matrix, promote the transfer of stress between the resin matrix and the fiber fabric, and then increase the bonding force between the fiber fabric and the functional materials such as the resin matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a working principle diagram of the clustering device of the present invention;
[0038] In the figure, 1, silk channel; 2, air flow channel; 3, filament bundle. DETAILED DESCRIPTION
[0039] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0041] A method for preparing highly laminating meta-aramid filaments, the preparation method comprising:
[0042] S1. Preparation of dried silk:
[0043] The meta-aramid polymer solution is subjected to dry-jet wet spinning, coagulation forming, stretching, water washing and drying operations to obtain dried yarn;
[0044] S2. Surface structure modification:
[0045] The dried filament bundle 3 enters the filament bundling device, and the surface of the fiber is structurally modified by high-pressure airflow to obtain a network-like fiber with a certain network degree and network fastness, namely, meta-aramid network fiber, which is then rolled up and doffed by a winding machine;
[0046] like Figure 1As shown, the filament bundling device comprises a filament path 1 and an air flow channel 2, wherein the air flow channel 2 is connected to the side of the filament path 1, and the filament bundle 3 to be surface structured passes through the filament path 1, and high-pressure gas is passed through the air flow channel 2;
[0047] S3. Heat treatment:
[0048] After the network-like fibers are unwound, they are subjected to heat setting treatment;
[0049] S4, interface enhancement modification:
[0050] After the heat treatment, in order to increase the bundling of the network yarns, reduce the generation of hairiness and fuzz, ensure the fiber flexibility and antistatic ability, and improve the lamination of the fiber with the resin matrix material, the heat-treated fibers are subjected to sizing treatment, and finally wound and doffed to obtain the highly laminating meta-aramid filament product; the fiber is subjected to sizing treatment to achieve fiber interface enhancement modification.
[0051] The sizing emulsion used in the sizing treatment comprises: a self-emulsifying cationic water-based sizing agent, a softener, an antistatic agent and water.
[0052] Specifically, the silk path is arranged horizontally, the air flow channel is vertically connected to the side of the silk path, and the air pressure in the air flow channel is 2-5 kg / cm 2 The silk channel and the air flow channel are both in the shape of a circular tube.
[0053] Specifically, when the fineness of the filament bundle 3 entering the filament bundling device is 50-266D, the diameter of the filament path 1 is 1.8-3.0 mm, the diameter of the airflow channel 2 is 0.7-0.9 mm, and the relationship between the airflow Q in the airflow channel 2 and the high-pressure gas pressure P in the airflow channel 2 is Q=1.043*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle 3 passing through the wire path 1 is 10-20m / min.
[0054] Specifically, when the fineness of the filament bundle 3 entering the filament bundling device is 300-600D, the diameter of the filament path 1 is 2.0-5.0 mm, the diameter of the airflow channel 2 is 0.9-1.1 mm, and the relationship between the airflow Q in the airflow channel 2 and the high-pressure gas pressure P in the airflow channel 2 is Q=1.353*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle 3 passing through the wire path 1 is 20-40m / min.
[0055] Specifically, the self-emulsifying cationic water-based sizing agent is an unsaturated polyester sizing agent or a cationic water-based polyurethane sizing agent;
[0056] The unsaturated polyester type sizing agent is prepared by reacting an amino modified resin with isophorone diisocyanate (IPDI); and the cationic waterborne polyurethane type sizing agent is prepared by reacting isophorone diisocyanate, 2,2-dihydroxymethyl propionic acid and triethylamine.
[0057] More specifically, the specific preparation method of the self-emulsifying cationic water-based sizing agent prepared by reacting an amino-modified epoxy resin with isophorone diisocyanate (IPDI) in the embodiment of the present invention is as follows: add isophorone diisocyanate (IPDI) and ethylene glycol monoallyl ether with a feed equivalent ratio of 1:1 to a glass reactor and react at 75°C for 2.5 hours to obtain an intermediate containing an unsaturated double bond, then add the amino-modified epoxy resin and the intermediate with a feed equivalent ratio of 1:1 to a reactor with an anchor stirrer, react at 60°C for 3 hours under nitrogen protection, and prepare an unsaturated polyester sizing agent. Other softeners and antistatic agents are added, wherein the mass proportion of the sizing agent is 25%, the mass proportion of the softener is 8%, the mass proportion of the antistatic agent is 10%, and the remaining components are deionized water, and are evenly mixed to form a sizing emulsion.
[0058] In the embodiment of the present invention, the preparation method of the self-emulsifying cationic water-based sizing agent prepared by the reaction of isophorone diisocyanate, 2,2-dimethylol propionic acid and triethylamine is as follows: add IPDI and adipic acid-1,4-butanediol with a feed equivalent ratio of 1:1.5 to a glass reactor, react at 80°C for 2h under a nitrogen environment, then reduce the reaction temperature to 55°C, add a dimethylformamide solution of 2,2-dimethylol propionic acid and heat it to 65°C for 1.2h, add epoxy resin and continue to react at a constant temperature for 4h to obtain an epoxy-modified water-based polyurethane prepolymer. The prepolymer is cooled to 30°C, the diluent acetone is added and stirred sufficiently, the neutralizer triethylamine is added to react for 30min, and then distilled DW water is added for emulsification. After a uniform and stable emulsion is formed, the chain extender diethylenetriamine aqueous solution is added dropwise to the reactor for about 20min, and the acetone is removed by reduced pressure distillation to obtain a cationic water-based polyurethane sizing agent. It is mixed with other softeners and antistatic agents, in which the sizing agent accounts for 18% by weight, the softener accounts for 10% by weight, the antistatic agent accounts for 12% by weight, and the remaining ingredient is deionized water, which are evenly mixed to form a sizing emulsion.
[0059] Specifically, in the sizing emulsion, the mass ratio of the self-emulsifying cationic aqueous sizing agent, the softener and the antistatic agent is (18-25): (8-10): (10-12);
[0060] The sizing emulsion is diluted with water to a mass concentration of 5.5-7% before being used for sizing.
[0061] More specifically, the softener used in the embodiment of the present invention is fatty alcohol polyoxyethylene ether, and the antistatic agent is phosphate ester, but the technical solution of the present invention is not limited to this one.
[0062] Specifically, in step S4, the sizing rate of the sizing treatment is 0.5-2.0%.
[0063] Specifically, in step S3, the heat treatment process is as follows: after the fiber is unwound, it is connected to a primary guide roller via a damping regulator, and is subjected to high-temperature heat setting via a heat pipe at a temperature of 300-450°C to increase its crystallinity, strength and rigidity; wherein the spinning speed is 30-50 m / min, the heating method is electric heating, and the temperature control range is ±0.5°C.
[0064] Specifically, the specific process in step S1 is:
[0065] S1-1, Spinning: The meta-aramid polymer stock solution passes through a metering pump at a spinning speed of 3-10 m / min, is accurately metered and squeezed into the spinneret assembly, and the filament bundle is ejected from the spinneret plate into the coagulation bath;
[0066] S1-2, coagulation molding: the filaments ejected from the spinneret are double diffused in a 50-70% mass concentration DMAC aqueous solution, DMSO aqueous solution or NMP aqueous solution to form primary fibers;
[0067] S1-3, stretching: the spun fiber is connected to the spinning disk through a guide wheel, and a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 40-60% is provided in the spinning disk as a secondary coagulation bath. The spun fiber is connected to a washing roller after passing through the spinning disk, and the fiber is stretched 2-5 times by adjusting the speed ratio between the spinning disk and the washing roller. During the stretching process, a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 30-50% is provided;
[0068] S1-4, washing: using immersion washing method, the fiber is washed in two steps: cold and hot water;
[0069] S1-5, drying: the washed fibers are dried at 90-150°C to obtain dried fibers.
[0070] Specifically, the viscosity of the meta-aramid polymer stock solution used in the embodiments of the present invention at 25° C. ranges from 500 to 800 poise.
[0071] More specifically, the meta-aramid polymer stock solution is prepared by a conventional low-temperature solution polycondensation process, and the specific preparation process is: adding meta-phenylenediamine to DMAc, DMSO or NMP, adding part of isophthaloyl chloride (85% of the total added mass) at 5-15°C for reaction, and then adding the remaining part of isophthaloyl chloride (15% of the total added mass) in three times at 25-35°C for reaction, adding calcium hydroxide for neutralization after the reaction, and adjusting the pH to 7.5-8. Finally, filtering and degassing to obtain a meta-aramid polymer stock solution with a viscosity range of 500-800 poise (25°C), wherein the molar ratio of the total amount of meta-phenylenediamine and isophthaloyl chloride is 1:1.
[0072] A highly laminating meta-aramid filament, wherein the meta-aramid filament is prepared according to the preparation method of the present invention.
[0073] An application of highly laminating meta-aramid filaments, wherein the meta-aramid filaments are applied in the field of self-lubricating materials.
[0074] Example 1
[0075] (1) Preparation of meta-aramid polymer stock solution: A low-temperature solution polycondensation process was used to prepare a meta-aramid polymer stock solution with a viscosity in the range of 600-800 poise (25°C) (the solvent was DMAc).
[0076] (2) Spinning: The meta-aramid polymer solution is accurately metered by a metering pump at a spinning speed of 6.2 m / min, and the filament bundle is sprayed out from the spinneret into the coagulation bath.
[0077] (3) Coagulation molding: The filaments ejected from the spinneret are double diffused with a DMAC aqueous solution with a mass concentration of 54.5±0.5% to form primary fibers.
[0078] (4) Stretching: The nascent fibers are connected to the spinning disk through a guide wheel. The spinning disk is provided with a DMAC aqueous solution with a mass concentration of 45.5±0.5% as a secondary coagulation bath. The fibers are stretched 3.5 times by adjusting the speed ratio between the spinning disk and the washing roller. During the stretching process, a DMAC aqueous solution with a mass concentration of 35±0.5% is provided as a stretching bath.
[0079] (5) Water washing: The fiber is washed in two steps of cold and hot water by immersion washing. The cold water washing is done in room temperature water, and the hot water washing is done in 50±5℃ hot water.
[0080] (6) Drying: After washing, the fiber is dried using a 90±5℃ steam roller.
[0081] (7) Surface structure modification: The drying wire adopts an internal pressure of 3.5kg / cm 2The high-pressure airflow filament bundling device uses high-pressure airflow construction technology to modify the fiber surface structure to form a network-like fiber with a certain network degree and network fastness, which is then rolled up and doffed by a winder. The front and rear end tension of the bundling device is 15±0.2cN.
[0082] In this embodiment, the diameter of the wire path of the bundling device is 2.5 mm, the diameter of the airflow channel is 0.8 mm, and the air flow rate Q in the airflow channel is 1.4081 m 3 / h, and the speed at which the filament bundle passes through the yarn path is 15m / min.
[0083] (8) Heat treatment: After unwinding, the fiber is connected to the primary guide roller through a damping regulator and subjected to high-temperature heat setting through a heat pipe at a temperature of 380°C. The heat drawing speed ratio is 1.3. The spinning speed is 35 m / min, the heating method is electric heating, and the temperature control range is ±0.5°C.
[0084] (9) Interface enhancement modification: After the fiber is heat-treated, in order to increase the clustering of the network yarn, reduce the generation of hairiness and hair, ensure the flexibility and antistatic ability of the fiber, and improve the adhesion between the fiber and the resin matrix material, a self-emulsifying cationic water-based sizing agent (unsaturated polyester sizing agent) is used. It is prepared from amino-modified resin and isophorone diisocyanate (IPDI) containing unsaturated double bond functional groups, and is matched with other softeners and antistatic agents. The sizing agent accounts for 25%, the softener accounts for 8%, the antistatic agent accounts for 10%, and the remaining ingredients are deionized water. They are evenly mixed to form an emulsion. The sizing emulsion with a concentration of 6±0.5% is prepared by diluting with deionized water, and the fiber is sizing to achieve fiber interface enhancement modification. Among them, the sizing rate is required to be 0.5~1.5%. The low sizing rate is beneficial for the application in the field of self-lubrication. The surface of the fabric remains relatively clean and smooth after desizing.
[0085] (10) Winding: The fibers are wound onto a bobbin by a winder to form meta-aramid filament products (seven groups of meta-aramid filament product samples were taken for testing). The physical indicators are shown in Table 1.
[0086] The test standards for physical performance indicators shall be implemented in accordance with Q / 0601 THX008-2020.
[0087] Table 1 Performance index data of meta-aramid filament of Example 1
[0088]
[0089] Example 2
[0090] (1) Preparation of meta-aramid polymer stock solution: A low-temperature solution polycondensation process was used to prepare a meta-aramid polymer stock solution (the solvent was DMSO) with a viscosity ranging from 500 to 700 poise (25°C).
[0091] (2) Spinning: The meta-aramid polymer stock solution is accurately metered by a metering pump at a spinning speed of 10.8 m / min, and the filament bundle is sprayed out from the spinneret into the coagulation bath.
[0092] (3) Coagulation molding: The filament bundle ejected from the spinneret undergoes double diffusion with a DMSO aqueous solution with a mass concentration of 50.5±0.5% to form primary fibers.
[0093] (4) Stretching: The spun fibers are connected to the spinning disk through a guide wheel. The spinning disk is provided with a DMSO aqueous solution with a mass concentration of 40.5±0.5% as a secondary coagulation bath. The fibers are stretched 4 times by adjusting the speed ratio between the spinning disk and the washing roller. A DMSO aqueous solution with a mass concentration of 30±0.5% is provided in the stretching path as a stretching bath.
[0094] (5) Water washing: The fiber is washed in two steps of cold and hot water by immersion water washing. The cold water washing is done in room temperature water, and the hot water washing is done in hot water at 70±5℃.
[0095] (6) Drying: After washing, the fiber is dried using a steam roller at 125±5℃.
[0096] (7) Surface structure modification: The drying wire adopts an internal pressure of 4.2kg / cm 2 The high-pressure airflow filament bundling device uses high-pressure airflow construction technology to modify the fiber surface structure to form a network-like fiber with a certain network degree and network fastness, which is then rolled up and doffed by a winding machine. The front and rear end tension of the bundling device is 25±0.2cN.
[0097] In this embodiment, the diameter of the wire path of the bundling device is 4.0 mm, the diameter of the airflow channel is 1.0 mm, and the air flow rate Q in the airflow channel is 1.9213 m 3 / h, and the speed at which the filament bundle passes through the yarn path is 30m / min.
[0098] (8) Heat treatment: After unwinding, the fiber is connected to the primary guide roller through a damping regulator and subjected to high-temperature heat setting through a heat pipe at a temperature of 400°C. The heat drawing speed ratio is 1.4. The spinning speed is 30m / min, the heating method is electric heating, and the temperature control range is ±0.5°C.
[0099] (9) Interface enhancement modification: After the fiber is heat-treated, in order to increase the bundling of the network yarn, reduce the generation of hairiness and hair, ensure the flexibility and antistatic ability of the fiber, and improve the adhesion between the fiber and the resin matrix material, a self-emulsifying cationic water-based sizing agent (cationic water-based polyurethane sizing agent) is used. It is prepared from isophorone diisocyanate (IPDI), 2,2-dihydroxymethyl propionic acid, and triethylamine, and is matched with other softeners and antistatic agents. The sizing agent accounts for 18%, the softener accounts for 10%, the antistatic agent accounts for 12%, and the remaining ingredients are deionized water. They are evenly mixed to form an emulsion. The sizing emulsion with a concentration of 6.5±0.5% is prepared by diluting with deionized water, and the fiber is sizing to achieve fiber interface enhancement modification. Among them, the sizing rate is required to be 0.5~2.0%. The low sizing rate is beneficial for the application in the field of self-lubrication. The surface of the fabric remains relatively clean and smooth after desizing.
[0100] (10) Winding: The fibers are wound onto a bobbin by a winder to form meta-aramid filament products (seven groups of meta-aramid filament product samples were taken for testing). The physical indicators are shown in Table 2 below.
[0101] The test standards for physical performance indicators shall be implemented in accordance with Q / 0601 THX008-2020.
[0102] Table 2 Performance index data of meta-aramid filament of Example 2
[0103]
[0104] Comparative Example 1
[0105] Conventional wet spinning is adopted, that is, high-pressure airflow construction technology is not used to prepare a network surface structure, and fiber surface modification cannot be achieved. The interface enhancement modification technology only plays a role in surface coating modification in this process, which is used to increase the cohesion and antistatic properties of the fiber semi-finished product. The other process conditions are the same as those in Example 2. The specific process is as follows:
[0106] (1) Preparation of meta-aramid polymer stock solution: a meta-aramid polymer stock solution having a viscosity in the range of 500-700 poise (25° C.). The meta-aramid polymer stock solution used in this comparative example 1 is the same as that used in example 2.
[0107] (2) Spinning: The meta-aramid polymer stock solution is accurately metered by a metering pump at a spinning speed of 10.8 m / min, and the filament bundle is sprayed out from the spinneret into the coagulation bath.
[0108] (3) Coagulation molding: The filament bundle ejected from the spinneret undergoes double diffusion with a DMSO aqueous solution with a mass concentration of 50.5±0.5% to form primary fibers.
[0109] (4) Stretching: The spun fibers are connected to the spinning disk through a guide wheel. The spinning disk is provided with a DMSO aqueous solution with a mass concentration of 40.5±0.5% as a secondary coagulation bath. The fibers are stretched 4 times by adjusting the speed ratio between the spinning disk and the washing roller. The stretching path is provided with a DMSO aqueous solution with a mass concentration of 30±0.5% as a stretching bath.
[0110] (5) Water washing: The fiber is washed in two steps of cold and hot water by immersion water washing. The cold water washing is done in room temperature water, and the hot water washing is done in hot water at 70±5℃.
[0111] (6) Drying: After washing, the fiber is dried using a steam roller at 125±5℃.
[0112] (7) Surface sizing: The dried silk is treated with a cationic water-based polyurethane sizing agent, which is prepared from isophorone diisocyanate (IPDI), 2,2-dihydroxymethyl propionic acid, triethylamine, etc., and is mixed with other softeners and antistatic agents, of which the sizing agent accounts for 18%, the softener accounts for 10%, the antistatic agent accounts for 12%, and the remaining ingredients are deionized water, which are evenly mixed to form an emulsion. The sizing emulsion with a concentration of 12±0.5% is prepared by diluting with deionized water, and the fiber is sizing. This process is a fiber surface coating modification to increase the cohesion and antistatic properties of the fiber semi-finished product. Among them, the sizing rate is required to be 3~5% to ensure the stability of the next step of heat treatment.
[0113] (8) Heat treatment: After unwinding, the fiber is connected to the primary guide roller through a damping regulator and subjected to high-temperature heat setting through a heat pipe at a temperature of 400°C. The heat drawing speed ratio is 1.4. The spinning speed is 30m / min, the heating method is electric heating, and the temperature control range is ±0.5°C.
[0114] (9) Winding: The fiber is wound and doffed by a winding machine to form a meta-aramid filament product (seven groups of meta-aramid filament product samples were taken for testing). The physical indicators are shown in Table 3. The test standard for physical performance indicators is implemented in accordance with Q / 0601 THX008-2020. It is worth noting that because the production process of this product is sizing first and then heat treatment, the sizing agent cannot be desized after high-temperature heat treatment, so it cannot be used in the field of self-lubrication.
[0115] Table 3 Performance index data of meta-aramid filament of comparative example 1
[0116]
[0117] From the comparison of the data results of Comparative Example 1 and Example 2, it can be seen that if the surface structure modification operation is not performed during the spinning process, the mechanical properties and index stability of the meta-aramid filament will be reduced. Moreover, without surface modification, in order to ensure the bundling and antistatic properties of the fiber, the fiber needs to be coated with sizing and then heat-treated, and the sizing agent cannot be desized after high-temperature heat treatment and has poor adhesion to the resin matrix, so it cannot be used in the field of self-lubrication.
[0118] Comparative Example 2
[0119] This comparative example 2 relies on a spinning process route of a highly laminated meta-aramid filament, and does not use the interface enhancement modification technology to introduce a "bridge" group on the fiber surface. Other process conditions are the same as those of Example 2. The specific process is as follows:
[0120] (1) Preparation of meta-aramid polymer stock solution: A low-temperature solution polycondensation process was used to prepare a meta-aramid polymer stock solution (the solvent was DMSO) with a viscosity ranging from 500 to 700 poise (25°C).
[0121] (2) Spinning: The meta-aramid polymer stock solution is accurately metered by a metering pump at a spinning speed of 10.8 m / min, and the filament bundle is sprayed out from the spinneret into the coagulation bath.
[0122] (3) Coagulation molding: The filament bundle ejected from the spinneret undergoes double diffusion with a DMSO aqueous solution with a mass concentration of 50.5±0.5% to form primary fibers.
[0123] (4) Stretching: The spun fibers are connected to the spinning disk through a guide wheel. The spinning disk is provided with a DMSO aqueous solution with a mass concentration of 40.5±0.5% as a secondary coagulation bath. The fibers are stretched 4 times by adjusting the speed ratio between the spinning disk and the washing roller. A DMSO aqueous solution with a mass concentration of 30±0.5% is provided in the stretching path as a stretching bath.
[0124] (5) Water washing: The fiber is washed in two steps of cold and hot water by immersion water washing. The cold water washing is done in room temperature water, and the hot water washing is done in hot water at 70±5℃.
[0125] (6) Drying: After washing, the fiber is dried using a steam roller at 125±5℃.
[0126] (7) Surface structure modification: The drying wire adopts an internal pressure of 4.2kg / cm 2 The high-pressure airflow filament bundling device uses high-pressure airflow construction technology to modify the fiber surface structure to form a network-like fiber with a certain network degree and network fastness, which is then rolled up and doffed by a winding machine. The front and rear end tension of the bundling device is 25±0.2cN.
[0127] In this embodiment, the diameter of the wire path of the bundling device is 4.0 mm, the diameter of the airflow channel is 1.0 mm, and the air flow rate Q in the airflow channel is 1.9213 m 3 / h, and the speed at which the filament bundle passes through the yarn path is 30m / min.
[0128] (8) Heat treatment: After unwinding, the fiber is connected to the primary guide roller through a damping regulator and subjected to high-temperature heat setting through a heat pipe at a temperature of 400°C. The heat drawing speed ratio is 1.4. The spinning speed is 30m / min, the heating method is electric heating, and the temperature control range is ±0.5°C.
[0129] (9) Winding: The fiber is wound into a bobbin by a winder to form a meta-aramid filament product (seven groups of meta-aramid filament product samples were taken for testing). The physical indicators are shown in Table 4. The test standard for physical performance indicators is implemented in accordance with Q / 0601 THX008-2020. It is worth noting that the meta-aramid filament prepared by this process has low physical indicators and serious hairiness. The fiber is a defective product, the bobbin cannot be unwound, and it cannot be used downstream.
[0130] Table 4 Performance index data of meta-aramid filament of comparative example 2
[0131]
[0132] From the comparison of the data results of Comparative Example 2 and Example 2, it can be seen that if the interface enhancement modification operation is not performed during the spinning process, the fiber bundling, bonding and antistatic properties are poor, and it is impossible to be normally wound into products. The obtained meta-aramid filaments have poor mechanical properties and serious hairiness, and are unqualified products. The silk package cannot be unwound and cannot be used by downstream customers.
[0133] Comparative Example 3
[0134] The same method as in Example 1 was adopted to prepare meta-aramid filaments, except that: in this comparative example 3, the size of the wire path was increased. In this comparative example 3, the diameter of the wire path was 4.5 mm (higher than the size specified in the present invention).
[0135] The physical indicators of the meta-aramid filaments prepared in this comparative example 3 are shown in Table 5 below.
[0136] Table 5 Performance index data of meta-aramid filament of comparative example 3
[0137]
[0138] From the comparison of the data of Example 1 and Comparative Example 3, it can be seen that: if the size of the wire path is increased, the impact force of the airflow on the wire strands will become smaller, and eddies parallel to the wire bundle cannot be generated. The monofilaments are in a low-frequency vibration state, and the monofilaments in the middle of the wire path are accelerated by the airflow, while the monofilaments on the side walls of the wire path are subjected to a smaller deflected airflow and cannot be joined with the middle monofilaments in the wire path for interlacing and entanglement, resulting in the entire wire bundle being loose and having no evenly distributed network nodes. The fibers are prone to breakage and entanglement when heat-treated, and the produced meta-aramid filaments have serious hairiness, poor mechanical properties and poor index stability, making them unqualified products that cannot be used downstream.
[0139] Comparative Example 4
[0140] The meta-aramid filaments were prepared by the same method as in Example 1, except that the size of the airflow channel was increased in Comparative Example 4. In Comparative Example 4, the diameter of the airflow channel was 1.1 mm (higher than the size specified in the present invention).
[0141] The physical indicators of the meta-aramid filaments prepared in this comparative example 4 are shown in Table 6 below.
[0142] Table 6 Performance index data of meta-aramid filament of comparative example 4
[0143]
[0144] From the data comparison of Example 1 and Comparative Example 4, it can be seen that if the size of the airflow channel is increased, the velocity of the jet airflow perpendicular to the filaments in the buncher will decrease, and eddies parallel to the filaments cannot be generated. The filament bundles are always in a low-frequency vibration state, and only the long filament bundles subjected to the force are intertwined and entangled, resulting in serious fiber looseness and no uniformly distributed network nodes. Severely loose fibers are very easy to break and entangle during heat treatment, and the produced fibers are seriously hairy and have poor mechanical properties. They are unqualified products and cannot be used downstream.
[0145] Comparative Example 5
[0146] The meta-aramid filaments were prepared by the same method as in Example 1, except that the size of the airflow channel was reduced in Comparative Example 5. In Comparative Example 5, the diameter of the airflow channel was 0.5 mm (lower than the size specified in the present invention).
[0147] The physical indicators of the meta-aramid filaments prepared in this comparative example 5 are shown in Table 7 below.
[0148] Table 7 Performance index data of meta-aramid filament of comparative example 5
[0149]
[0150] From the data comparison of Example 1 and Comparative Example 5, it can be seen that if the size of the airflow channel is reduced, the jet airflow velocity perpendicular to the filaments in the bundler will be too large, the eddy current generated will not be parallel to the filaments, the airflow force on the single filament bundle will be uneven, the fibers cannot be evenly intertwined and entangled in the filament channel, the whole filament bundle will diverge and have serious hairy fibers, and there will be no evenly distributed network nodes. The fiber is prone to breakage and entanglement during heat treatment, the produced fiber has serious hairy fibers and poor mechanical properties, and is a substandard product that cannot be used downstream.
[0151] Comparative Example 6
[0152] The meta-aramid filaments were prepared by the same method as in Example 1, except that: in this comparative example 6, the pressure of the high-pressure gas was increased, and in this comparative example 6, a 6kg / cm 2 High pressure gas. (Higher than the gas pressure defined in the present invention).
[0153] The physical indicators of the meta-aramid filaments prepared in this comparative example 6 are shown in Table 8 below.
[0154] Table 8 Performance index data of meta-aramid filament of comparative example 6
[0155]
[0156] From the comparison of the data of Example 1 and Comparative Example 6, it can be seen that if the pressure of the high-pressure gas is increased, the jet airflow perpendicular to the filaments will be too large, the filament bundle will be in a high-frequency vibration state, the filament bundle will be intertwined and tangled, and cannot be opened, resulting in the fiber having no uniformly distributed network nodes. At the same time, the high-pressure airflow will damage the surface of the filament bundle to produce a large number of fine filaments, which are easy to break and entangle during heat treatment. The produced fiber has serious filaments and poor mechanical properties, and is a substandard product that cannot be used downstream.
[0157] Comparative Example 7
[0158] The same method as in Example 2 was adopted to prepare meta-aramid filaments, except that the sizing agent in this comparative example 7 was replaced with a sizing agent of model 8588 which is commonly purchased on the market.
[0159] The physical indicators of the meta-aramid filaments prepared in this comparative example 7 are shown in Table 9 below.
[0160] Table 9 Performance index data of meta-aramid filament of comparative example 7
[0161]
[0162] From the comparison of the data of Example 2 and Comparative Example 7, it can be seen that the surface treatment of the fiber using the commonly used sizing agent on the market is a surface coating process, which serves to increase the fiber's bundling and reduce the fiber's electrostatic effect, but does not achieve fiber surface functionalization, and its fiber mechanical properties are slightly lower than the fiber properties obtained by using the sizing agent defined in the present invention to perform interfacial enhancement modification on the fiber. However, the fiber treated with the sizing agent cannot be desized on the one hand, and on the other hand, the fiber has poor adhesion to the resin and cannot be used in the field of self-lubrication.
[0163] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0164] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing highly laminating meta-aramid filaments, characterized in that: The preparation method is: S1. Preparation of dried silk: The meta-aramid polymer solution is subjected to dry-jet wet spinning, coagulation forming, stretching, water washing and drying operations to obtain dried yarn; S2. Surface structure modification: The dried filament bundle enters a filament bundling device, and the surface of the fibers in the filament bundle is structurally modified by a high-pressure airflow to obtain a network-like fiber, which is then rolled up and doffed by a winding machine; The filament bundling device comprises a filament path and an air flow channel, wherein the air flow channel is communicated with the side of the filament path, the filament bundle to be surface structure treated passes through the filament path, and high-pressure gas is passed through the air flow channel; S3. Heat treatment: After the network-like fibers are unwound, they are subjected to heat setting treatment; S4, interface enhancement modification: The heat-treated fibers are sizing treated, and finally wound and doffed to obtain the highly laminating meta-aramid filament product; The sizing emulsion used in the sizing treatment comprises: a self-emulsifying cationic water-based sizing agent, a softener, an antistatic agent and water; The silk path is arranged horizontally, the air flow channel is vertically connected to the side of the silk path, and the air pressure in the air flow channel is 2-5kg / cm 2 of high pressure gas; The fineness of the filament bundle entering the filament bundling device is 50-266D or 300~600D; When the fineness of the filament bundle entering the filament bundling device is 50-266D, the diameter of the filament path is 1.8-3.0 mm, the diameter of the airflow channel is 0.7-0.9 mm, and the relationship between the airflow Q in the airflow channel and the high-pressure gas pressure P in the airflow channel is Q=1.043*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle passing through the wire path is 10-20m / min; When the fineness of the filament bundle entering the filament bundling device is 300-600D, the diameter of the filament path is 2.0-5.0mm, the diameter of the airflow channel is 0.9-1.1mm, and the relationship between the airflow Q in the airflow channel and the high-pressure gas pressure P in the airflow channel is Q=1.353*(P+1), where the unit of the airflow Q is m 3 / h, the unit of high-pressure gas pressure P is bar; the speed of the filament bundle passing through the wire path is 20-40m / min; The self-emulsifying cationic water-based sizing agent is an unsaturated polyester sizing agent or a cationic water-based polyurethane sizing agent; The unsaturated polyester sizing agent is prepared by reacting an amino-modified resin with isophorone diisocyanate; the cationic waterborne polyurethane sizing agent is prepared by reacting isophorone diisocyanate, 2,2-dimethylol propionic acid and triethylamine; In the sizing emulsion, the mass ratio of the self-emulsifying cationic aqueous sizing agent, the softener and the anti-static agent is (18-25): (8-10): (10-12); The mass concentration of the sizing emulsion is 5.5-7%.
2. The method for preparing a highly bondable meta-aramid filament according to claim 1, characterized in that: In step S4, the sizing rate of the sizing treatment is 0.5-2.0%.
3. The method for preparing a highly laminated meta-aramid filament according to claim 1, characterized in that: In step S3, the temperature of the heat setting treatment is 300-450°C, and the spinning speed is 30-50 m / min.
4. The method for preparing a highly laminated meta-aramid filament according to claim 1, characterized in that: The specific process in step S1 is: S1-1, Spinning: The meta-aramid polymer stock solution passes through a metering pump with a spinning speed of 3-10 m / min, and is accurately metered and squeezed into the spinneret assembly, and the filament bundle is ejected from the spinneret plate into the coagulation bath; S1-2, coagulation molding: the filaments ejected from the spinneret are double diffused in a 50-70% mass concentration DMAC aqueous solution, DMSO aqueous solution or NMP aqueous solution to form primary fibers; S1-3, stretching: the spun fiber is connected to the spinning disk through a guide wheel, and a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 40-60% is provided in the spinning disk as a secondary coagulation bath. The spun fiber is connected to a washing roller after passing through the spinning disk, and the fiber is stretched 2-5 times by adjusting the speed ratio between the spinning disk and the washing roller. During the stretching process, a DMAC aqueous solution, a DMSO aqueous solution or an NMP aqueous solution with a mass concentration of 30-50% is provided; S1-4, washing: using immersion washing method, the fiber is washed in two steps: cold and hot water; S1-5, drying: the washed fibers are dried at 90-150°C to obtain dried fibers.
5. A highly laminating meta-aramid filament, characterized in that: The meta-aramid filament is prepared according to the preparation method according to any one of claims 1 to 4.
6. An application of the high-bonding meta-aramid filament according to claim 5, characterized in that: The meta-aramid filament is used in the field of self-lubricating materials.
Citation Information
Patent Citations
Aramid III fiber reinforced self-lubricating gasket composite material and preparation method thereof
CN113089327A
MXene-nano aramid fiber modified PTFE composite material and preparation method and application thereof, resin-based fiber fabric self-lubricating material and preparation method and application thereof
CN118390292A
Surface treatment method of aramid fiber III
CN101787647A
Preparation method of modified aramid-thermoplastic polyurethane composite material
CN109096742A